The Influence of Qris Adoption and Financial Technology Knowledge on the Quality of Accounting Information and Financial Decisions (Empirical Study on MSMEs in Setu District, Bekasi) - Bella Fitri Melliya Sari; Rina Pratiwi; Karsam (Indonesian Journal of Business Analytics, 2026)
This study examines how QRIS adoption and fintech knowledge shape the quality of accounting information and financial decision-making among MSME actors in Setu District, Bekasi. A quantitative design was employed, with survey data gathered from 61 MSME respondents chosen through a sampling procedure and processed via multiple linear regression in SPSS. Findings indicate that both QRIS adoption and fintech knowledge exert a significant positive influence on accounting information quality as well as on financial decisions. In other words, greater reliance on digital payment tools together with a stronger grasp of fintech concepts tends to strengthen how MSME actors manage financial data and make business-related choices. What distinguishes this study is its incorporation of financial-processing indicators within the accounting information construct, contributing a fresh angle to accounting information systems research.